2018
DOI: 10.5853/jos.2017.00178.e1
|View full text |Cite
|
Sign up to set email alerts
|

Penumbral Imaging-Based Thrombolysis with Tenecteplase Is Feasible up to 24 Hours after Symptom Onset

Abstract: We apologize for any inconvenience that this may have caused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Michel et al [14] randomly assigned stroke patients occurring in the middle cerebral artery territory to alteplase venous thrombolysis, with an average last proof of well-being time point of 564 min (9.4 h), or placebo, and an average last proof of well-being of 437.5 min (7.3 h), and the results showed that thrombolytic therapy is feasible in patients with unknown stroke. Kate et al [15] reported patients were treated with tenecteplase at a median of 9.6 h after symptom onset with a range of 5.1 to 23.7 h and supported the feasibility of tenecteplase treatment in patients with 4 to 24 h of ischemic penumbral onset. In addition, we also performed subgroup analysis through different ages, NIHSS scores, and time windows and demonstrated that patients in the IVT group had better favorable functional outcomes at age ≤70 years, NIHSS ≤10, and time windows >9 h than the patients in the CG.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Michel et al [14] randomly assigned stroke patients occurring in the middle cerebral artery territory to alteplase venous thrombolysis, with an average last proof of well-being time point of 564 min (9.4 h), or placebo, and an average last proof of well-being of 437.5 min (7.3 h), and the results showed that thrombolytic therapy is feasible in patients with unknown stroke. Kate et al [15] reported patients were treated with tenecteplase at a median of 9.6 h after symptom onset with a range of 5.1 to 23.7 h and supported the feasibility of tenecteplase treatment in patients with 4 to 24 h of ischemic penumbral onset. In addition, we also performed subgroup analysis through different ages, NIHSS scores, and time windows and demonstrated that patients in the IVT group had better favorable functional outcomes at age ≤70 years, NIHSS ≤10, and time windows >9 h than the patients in the CG.…”
Section: Discussionmentioning
confidence: 86%
“…The flow diagram was summarized [Figure 1]. A total of five trials were finally evaluated [14–18] . After reading the full text, only four RCTs [14,16–18] involving 848 patients met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…5 Phase II studies indicated a potential benefit of tenecteplase for the treatment of AIS, [6][7][8] and a proof of concept study demonstrated feasibility of treatment up to 24 h after onset. 9 The most recent American Heart Association/American Stroke Association (AHA/ ASA) AIS guidelines recognized tenecteplase as a reasonable alternative to alteplase in limited patient populations. 10 This trial will evaluate whether treatment with IV tenecteplase, administered 4.5-24 h after a patient's last-known well time with or without endovascular thrombectomy (EVT), is superior to placebo in patients who have a large vessel occlusion (LVO) and evidence of salvageable tissue on their baseline computed tomography (CT) perfusion or magnetic resonance perfusion imaging.…”
Section: Introduction and Rationalementioning
confidence: 99%
“…5 Phase II studies indicated a potential benefit of tenecteplase for the treatment of AIS, 68 and a proof of concept study demonstrated feasibility of treatment up to 24 h after onset. 9 The most recent American Heart Association/American Stroke Association (AHA/ASA) AIS guidelines recognized tenecteplase as a reasonable alternative to alteplase in limited patient populations. 10…”
Section: Introduction and Rationalementioning
confidence: 99%
“…In the EXTEND trial, evidence has shown thrombolysis with rt-PA to be effective and improve overall outcome when administered in a window of 4.5-9 hours after symptom onset [ 17 , 18 ]. Along these lines, imaging-based intravenous thrombolysis with Tenecteplase is efficacious up to 24 hours after symptom onset in selected patients [ 19 ]. A study reanalyzed the data of the DEFUSE 3 trial and suggested that approximately 20% of patients with LVO who are not treated with thrombectomy had a salvageable penumbra for at least an additional 24 hours [ 20 ].…”
Section: Introductionmentioning
confidence: 99%